Experimental Study on Pressure Drop Characteristics of Vents - Dhanushkodi, Ganesan (IEEE transactions on components and packaging technologies, 2010)
One of the major impacts on the thermal design of electronic systems over the past decade has been the use of computational fluid dynamics and heat transfer tools. System level thermal simulation has driven the need to understand the performance and the reliability aspects of boundary conditions. In addition to the modeling inaccuracies, computation results also reflect the influence of the accuracy of input parameters. The computational fluid dynamics model of electronic enclosures requires the pressure drop details of vents to predict the system impedance and air flow through the system thereafter. The temperature of electronic components depends on the rate of airflow through the electronic system. Loss coefficient of vents appears to be the major source of error. The modeling of each vent is typically not possible and is represented by its pressure drop. An experimental setup is established to measure the pressure drop characteristics of different patterns of vents commonly used in electronic equipment. Pressure drop of different vent patterns, with hole diameter varying from 1.6 mm to 3.0 mm, the pitch varying from 3.2 mm to 6.5 mm, and the porosity varying from 20% to 45%, are measured using an experimental setup. In this paper, a practical formula for the loss coefficient of vents is presented. This formula takes into account important parameters such as hole diameter, pitch, porosity, and Reynolds number.